A novel humanized MUC1 antibody–drug conjugate for the treatment of trastuzumab-resistant breast cancer. (29th September 2021) - Wu, Guang; Li, Lan; Qiu, Yuxin; Sun, Wei; Ren, Tianhao; Lv, Yingshuai; Liu, Mengnan; Wang, Xiaoxia; Tao, Hongqun; Zhao, Lingjie; Cao, Jiawei; He, Licai; et al.
Abstract: Mucin 1 (MUC1) has been regarded as an ideal target for cancer treatment, since it is overexpressed in a variety of different cancers including the majority of breast cancer. However, there are still no approved monoclonal antibody drugs targeting MUC1. In this study, we generated a humanized MUC1 (HzMUC1) antibody from our previously developed MUC1 mouse monoclonal antibody that only recognizes MUC1 on the surface of tumor cells. Furthermore, an antibody–drug conjugate (ADC) was generated by conjugating HzMUC1 with monomethyl auristatin (MMAE), and the efficacy of HzMUC1-MMAE on the MUC1-positive HER2+ breast cancer in vitro and in 'Xenograft' model was tested. Results from western blot analysis and immunoprecipitation revealed that the HzMUC1 antibody did not recognize cell-free MUC1-N in sera from breast cancer patients. Confocal microscopy analysis showed that HzMUC1 antibody bound to MUC1 on the surface of breast cancer cells. Results from mapping experiments suggested that HzMUC1 may recognize an epitope present in the interaction region between MUC1-N and MUC1-C. Results from colony formation assay and flow cytometry demonstrated that HzMUC1-MMAE significantly inhibited cell growth by inducing G2/M cell cycle arrest and apoptosis in trastuzumab-resistant HER2-positive breast cancer cells. Meanwhile, HzMUC1-MMAE significantly reduced the growth of HCC1954 xenograft tumors by inhibiting cell proliferation and enhancing cell death. In conclusion, our results indicate that HzMUC1-ADC is a novel therapeutic drug that can overcome trastuzumab resistance of breast cancer. HzMUC1-ADC should also be an effective therapeutic drug for the treatment of different MUC1-positive cancers in clinic.